Pilot’s Handbook of Aeronautical Knowledge - Administration, Federal Aviation (Open textbook library., 2023)
The Pilot’s Handbook of Aeronautical Knowledge (PHAK) is an essential book for any Remote, Sport, Recreational, Private, Commercial, and Instructor Pilot. It provides basic knowledge that is vital for all pilots. This handbook introduces pilots to the broad spectrum of knowledge that will be needed as they progress in their pilot training. This handbook is useful to beginning pilots, as well as those pursuing more advanced pilot certificates.